2005
DOI: 10.1098/rspb.2005.3353
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent diet choice in an avian top predator

Abstract: Age-dependent breeding performance is arguably one of the best-documented phenomena in ornithology. The existence of age-related trends has major implications for life-history theory, but the proximate reasons for these patterns remain poorly understood. It has been proposed that poor breeding performance of young individuals might reflect lack of foraging skills. We investigated this possibility in a medium-sized, powerful raptor-the northern goshawk Accipiter gentilis. Male goshawks are responsible for provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 36 publications
1
94
0
Order By: Relevance
“…2). The association between foraging efficiency and TL is similar to the pattern of increasing efficiency with chronological age found in goshawks (Rutz et al 2006). Murres become more efficient foragers as their telomeres are deteriorated.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…2). The association between foraging efficiency and TL is similar to the pattern of increasing efficiency with chronological age found in goshawks (Rutz et al 2006). Murres become more efficient foragers as their telomeres are deteriorated.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, we predict birds with deteriorated telomeres will spend less time underwater, indicating decreased foraging efficiency. Foraging efficiency declines with age in several seabird species (Oro et al 2014) and may be a driver of aging patterns overall (Lecomte et al 2010), although in some species foraging efficiency or success increased with age (Desrochers 1992, Rutz et al 2006, Le Vaillant et al 2013. Lastly, we predict that the stable isotope signatures of birds with short telomeres will indicate more inshore prey (if they forage closer to the colony) and lower trophic levels, since they cannot specialize on high quality, high trophiclevel prey.…”
Section: Introductionmentioning
confidence: 99%
“…Although there were no categorical age differences among sharpshinned hawks, when body mass was included as a covariate, grip force increased more rapidly with mass in adults than it did in juveniles. Rutz et al found that as male northern goshawks (Accipiter gentilis) age, they take pigeons in greater proportions, presumably because they are more difficult for younger hawks to procure (Rutz et al, 2006). Although it is unclear specifically how young males are limited in their hunting abilities, our results for congeneric Cooper's and sharp-shinned hawks suggest that a deficiency in grip force may be a potential source of reduced predatory performance that restricts them from a portion of the prey resource spectrum.…”
Section: Discussion Bite and Grip Forces Of Accipiters And Falconsmentioning
confidence: 99%
“…We converted bird counts into relative biomass estimates (territories!2!mean adult body mass) before fledgling production, using body mass values given in Bijlsma (1993). Across ecological scales, goshawk biology is intimately linked to the availability of pigeon prey (Rutz 2005b;Rutz et al 2006). Pigeons form the prey-base of most western European goshawk populations, including those in The Netherlands (review: Rutz et al in press), and we therefore collected additional data in our study to assess trends in local populations.…”
Section: Methodsmentioning
confidence: 99%